A more effective method to produce the crushed frozen saline solution required for organ transplants (2020)
The present report exhibits the ideation, prototyping, construction and testing of d'frost, an alternative device to crush the frozen saline solution (FFS) that is within a double plastic bag and is used in organ transplant surgeries. The need to create d'frost arose from an observation stage performed in two organ rescue surgeries in different health institutions: Hospital Santa Clara and Clinica Nueva El Lago, both in Bogotá, Colombia. e Med identified that the current process to crush the FSS is performed by nurses who lay on their knees with a small mallet and hit repeatedly the bag of the FSS until it has the required texture. This is a rudimentary procedure that affects the nursing assistants health. On account of the observation stage, the high volume of transplant surgeries that take place worldwide and the need of an efficient crushing of the FSS method in order to avoid health issues in nurses, e Med performed an exhaustive prototyping stage to acquire valuable data and choose the appropriate mechanism and design of d'frost. Consequently, was satisfactorily chosen the pressure principle as the mechanism of the device. d'frost consists of a pneumatic chipper that performs a repetitive striker movement with a modified drill bit made of 304 stainless steel, which has a trigger activated revolution. Additionally, d'frost is accompanied by a stand which ensures user safety. The financial model for d'frost sales is profitable since an expansion towards other countries is projected. Concerning the competitive advantage of d'frost, it is the most cost-effective compared with devices on the market that have the same functionality. Despite the device limitations, d'frost is a more effort-effective alternative to crush the FSS bag than the current method, and is intended to be implemented on operating rooms and powered by a compressed air line.